Stability of trapped degenerate dipolar Bose and Fermi gases - Adhikari, S. K. [UNESP] (IOP Publishing, 2013)
Trapped degenerate dipolar Bose and Fermi gases of the cylindrical symmetry with the polarization vector along the symmetry axis are only stable for the strength of dipolar interaction below a critical value. In the case of bosons, the stability of such a dipolar Bose-Einstein condensate (BEC) is investigated for different strengths of contact and dipolar interactions using a variational approximation and a numerical solution of a mean-field model. In the disc shape, with the polarization vector perpendicular to the plane of the disc, the atoms experience an overall dipolar repulsion and this fact should contribute to the stability. However, a complete numerical solution of the dynamics leads to the collapse of a strongly disc-shaped dipolar BEC due to the long-range anisotropic dipolar interaction. In the case of fermions, the stability of a trapped single-component degenerate dipolar Fermi gas is studied including the Hartree-Fock exchange and Brueckner-Goldstone correlation energies in the local-density approximation valid for a large number of atoms. Estimates for the maximum allowed number of polar Bose and Fermi molecules in the BEC and degenerate Fermi gas are given. © 2013 IOP Publishing Ltd.
Keywords: Bose-Einstein condensates; Correlation energy; Cylindrical symmetry; Dipolar interaction; Hartree-Fock exchanges; Numerical solution; Polarization vectors; Variational approximation; Atoms; Electron gas; Polarization; Stability; Statistical mechanics; Fermions